(untitled) (International Current Pharmaceutical Journal, 2012)
Two simple, accurate, precise, reproducible and economical UV spectroscopic methods (A & B) for simultaneous estimation of Ciprofloxacin and Tinidazole in tablet dosage form have been developed. Method A employs solving of simultaneous equations based on the measurement of absorbance at two wavelengths, 271nm and 318nm which are the ?max values of Ciprofloxacin and Tinidazole respectively in phosphate buffer (pH 6.8). Method B is based on the principle of Q-Analysis where in the absorbance was measured at 292nm (iso-absorptive point) and 271nm (?max of Ciprofloxacin)in phosphate buffer (pH 6.8). Ciprofloxacin and Tinidazole shows linearity at all the selected wave-lengths and obeys Beers law in the concentration range of 10-35µg/mL and 10-80µg/mL respectively. Recovery studies for Ciprofloxacin and Tinidazole were performed and the percentage recovery for both the drugs was obtained in the range of 98.1-99.7% (Method A) and 98.0-100.4% (Method B) confirming the accuracy of the proposed method. Both the methods showed good reproducibility and recovery with %RSD less than 2. Statistical validation of the data shows that the proposed methods can be successfully applied for the routine analysis of drugs in commercial tablets. DOI: http://dx.doi.org/10.3329/icpj.v1i10.11849 International Current Pharmaceutical Journal 2012, 1(10): 317-321